Anti-radiation high-purity quartz glass, and preparation method, device and optical fiber thereof

By preparing high-purity quartz glass, using flame hydrolysis reaction and multi-step processing technology, the radiation resistance is improved, the problem of color center defects in radiated environments is solved, and the optical fiber signal transmission performance is improved.

CN119874177APending Publication Date: 2025-04-25SHANGHAI UNIV +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411982288.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

Quartz glass is prone to color-center defects in the radiation environment, resulting in an increase in attenuation of the optical fiber and affecting signal transmission performance.

Method used

High-purity quartz glass is used to prepare high-hydroxyl content and uniformly distributed radiation-resistant high-purity quartz glass through flame hydrolysis reaction and multi-step treatment (pretreatment, vitrification and purification treatment), to inhibit the occurrence of color center defects.

Benefits of technology

It improves the radiation resistance of high-purity quartz glass for radiation resistance, reduces the attenuation of optical fibers, and improves the signal transmission performance of optical fibers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119874177A_ABST
    Figure CN119874177A_ABST
Patent Text Reader

Abstract

The invention provides anti-radiation high-purity quartz glass and a preparation method, device and optical fiber thereof, the anti-radiation high-purity quartz glass comprises hydroxyl, and the mass content of the hydroxyl in the anti-radiation high-purity quartz glass is greater than or equal to 300ppm. The fluctuation of the axial hydroxyl mass content in the high-purity quartz glass for radiation resistance does not exceed 15 ppm, and the fluctuation of the radial hydroxyl mass content in the high-purity quartz glass for radiation resistance does not exceed 15 ppm. The anti-radiation high-purity quartz glass provided by the invention is high in hydroxyl content and uniform in hydroxyl content distribution, and generation of color center defects can be inhibited, so that the radiation resistance of the anti-radiation high-purity quartz glass is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to quartz glass, in particular to high-purity quartz glass for radiation resistance and a preparation method, device and optical fiber thereof, belonging to the field of quartz glass preparation. Background Art

[0002] Quartz glass is an amorphous material composed of a single component of silicon dioxide. Therefore, it has many advantages such as high temperature resistance, strong chemical stability, high purity, good transmittance, and radiation resistance. It is widely used in advanced optics, semiconductors, photovoltaics, aerospace, optical fiber and other fields.

[0003] However, when quartz glass is used as an optical fiber in special environments such as radiation, high-energy or high-dose electrons, neutrons, rays, etc. will interact with the quartz optical fiber, causing color center defects in the network structure of the quartz glass, causing its structure to change. This defect will cause absorption in specific bands (especially ultraviolet and visible light fluctuations), resulting in increased attenuation of the optical fiber and a decrease in the signal transmission performance of the optical fiber.

[0004] Therefore, how to overcome the increase in optical fiber attenuation caused by color center defects is an urgent problem to be solved by those skilled in the art. Summary of the invention

[0005] The present invention provides high-purity quartz glass for radiation resistance and a preparation method, device and optical fiber thereof. The high-purity quartz glass for radiation resistance has a high hydroxyl content and a uniform distribution of the hydroxyl content, and can inhibit the generation of color center defects, thereby improving the radiation resistance of the high-purity quartz glass for radiation resistance.

[0006] The present invention provides a method for preparing high-purity quartz glass for radiation resistance. The preparation method can prepare high-purity quartz glass for radiation resistance with a high hydroxyl content, and the hydroxyl content in the high-purity quartz glass for radiation resistance is uniformly distributed. At the same time, the preparation method has simple process, low equipment requirements and low energy consumption, which is conducive to the industrial production of high-purity quartz glass for radiation resistance.

[0007] The present invention also provides a device for preparing the above-mentioned radiation-resistant high-purity quartz glass. The device has a simple composition and low cost, and lays a foundation for the industrial production of radiation-resistant high-purity quartz glass.

[0008] The present invention also provides an optical fiber, which is made of the above-mentioned high-purity quartz glass for radiation resistance and has high radiation resistance.

[0009] The present invention provides high-purity quartz glass for radiation resistance, comprising hydroxyl groups, wherein the mass content of the hydroxyl groups in the high-purity quartz glass for radiation resistance is greater than or equal to 300 ppm, the fluctuation of the mass content of the hydroxyl groups in the axial direction of the high-purity quartz glass for radiation resistance does not exceed 15 ppm, and the fluctuation of the mass content of the hydroxyl groups in the radial direction of the high-purity quartz glass for radiation resistance does not exceed 15 ppm.

[0010] Optionally, the impurity content of the high-purity quartz glass for radiation resistance is lower than 1 ppb, and the optical uniformity of the high-purity quartz glass for radiation resistance is 1-5 ppm.

[0011] The present invention provides a method for preparing the radiation-resistant high-purity quartz glass as described above, comprising the following steps: 1) subjecting a mixed gas of SiCl4, O2, H2, and Ar to a flame hydrolysis reaction under a negative pressure of 20-35 Pa to obtain a silicon dioxide deposit; 2) subjecting the silicon dioxide deposit to a pretreatment, a vitrification treatment, and a purification treatment in sequence to obtain the radiation-resistant high-purity quartz glass.

[0012] Optionally, the length of the silica deposit is 900-1500 mm, the diameter 2R of the silica deposit is 100-300 mm, and the ratio of h to R is 0.1-0.8; wherein R is the radius of the silica deposit, and h is the distance between the diameter change point and the end of the silica deposit.

[0013] Optionally, step 1) includes the following steps: under a negative pressure of 20-35Pa, the mixed gas of SiCl4, O2, H2, and Ar is passed through a blowtorch to perform the flame hydrolysis reaction, and silicon dioxide is deposited on the target rod to obtain the silicon dioxide deposit body; the angle θ between the axis of the blowtorch and the axis of the target rod is 30-50°, the distance L1 between the port of the blowtorch and the axis of the target rod is 80-180mm, and the vertical distance between the port of the blowtorch and the axis of the target rod is L2, L2:L1=0.5-0.76.

[0014] Optionally, the rotation speed of the target rod is 10-40rpm, the deposition rate of silicon dioxide is 0.3-1.5mm / min; the flow ratio of SiCl4 to O2 is (1-2):(2-1), the flow ratio of H2 to O2 is (1-3):1, and the flow rate of SiCl4 is 20-40g / min.

[0015] Optionally, the pretreatment includes the following steps: 1) rotating the silica deposit at a rotation speed of 3-6rpm under a negative pressure of 0.2-0.5bar for 1-3h; 2) introducing a water mist with a flow rate of 1000-3000mL / h into the space where the silica deposit is set at 200-400°C and 8-15Pa for 4-8h; wherein the particle size of the water mist is 3-10μm; 3) introducing a water mist with a flow rate of 1000-3000mL / h and an O2 with a flow rate of 2-6L / min at 300-600°C and 10-30Pa for 12-24h to obtain a first intermediate.

[0016] Optionally, the vitrification treatment includes the following steps: at 1300-1500° C., introducing water mist with a flow rate of 1000-3000 mL / h, O2 with a flow rate of 2-6 L / min, and He with a flow rate of 8-25 L / min into the space where the first intermediate is set, and maintaining for 4-6 hours to obtain a second intermediate.

[0017] Optionally, the purification treatment includes the following steps: cooling the second intermediate to less than 100°C for 30-60 minutes; after the second intermediate is cooled, introducing a H2, Ar mixed gas with a flow rate of 3-5L / min and a He with a flow rate of 3-5L / min into the space where the second intermediate is set at a negative pressure of 0.3-0.6bar until the pressure of the space is a positive pressure of 0.5-2bar, raising the temperature to 400-800°C at a heating rate of 10-20°C / min, and maintaining constant temperature and pressure for 60-150h to obtain the radiation-resistant high-purity quartz glass; wherein the volume proportion of H2 in the H2, Ar mixed gas is 1-3%.

[0018] The present invention provides a device, comprising a flame hydrolysis reaction unit, a pretreatment unit, a vitrification treatment unit and a purification treatment unit; the flame hydrolysis reaction unit is used for the flame hydrolysis reaction; the pretreatment unit is used for the pretreatment; the vitrification treatment unit is used for the vitrification treatment; and the purification treatment unit is used for the purification treatment.

[0019] The present invention provides an optical fiber, which is made of the radiation-resistant high-purity quartz glass as described above.

[0020] The present invention provides high-purity quartz glass for radiation resistance and a preparation method, device and optical fiber thereof. The high-purity quartz glass for radiation resistance contains hydroxyl groups with a mass percentage content greater than or equal to 300 ppm in the structure, which can form Si-OH, thereby inhibiting the generation of color center defects, and further improving the radiation resistance of the high-purity quartz glass for radiation resistance; and the hydroxyl groups in the high-purity quartz glass for radiation resistance are evenly distributed, which can ensure the uniformity of the silicon dioxide network structure, avoid the generation of deformed structures, reduce the structural stress of the glass, and thus improve the radiation resistance of the high-purity quartz glass for radiation resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 is a schematic diagram of the bottom dimensions of the silicon dioxide deposit;

[0022] Figure 2 It is a schematic diagram of the angle between the axis of the blowtorch and the axis of the target rod and the distance between the blowtorch port and the axis of the target rod;

[0023] Figure 3 is a schematic diagram of the heat treatment process of the silicon dioxide deposit;

[0024] Figure 4 is a schematic diagram of a deposition device;

[0025] Figure 5 is a schematic diagram of a sintering furnace;

[0026] Figure 6 1 is a radial hydroxyl content distribution diagram of Example 1 and Comparative Example 1;

[0027] Figure 7 : is the radial hydroxyl content distribution diagram of Example 4 and Comparative Example 3;

[0028] Figure 8 The axial rod diameter distribution diagram of the powders of Example 2 and Comparative Example 1;

[0029] Fig. 9 This is the spectral loss diagram of the optical fiber prepared in Example 2 after radiation treatment.

[0030] Reference numerals:

[0031] R - radius of the silica deposit;

[0032] h-the distance between the diameter change point and the end of the silica deposit;

[0033] 1- Blowtorch;

[0034] 2- Air supply system;

[0035] 3- Pressure control console;

[0036] 4- Exhaust system;

[0037] 5-Deposition boom;

[0038] 6-Pressure detector;

[0039] 7-target stick;

[0040] 8-silicon dioxide deposit;

[0041] 9- deposition chamber;

[0042] 10-CCD camera;

[0043] 11-Silica deposition imaging diameter measurement system;

[0044] 12-Raw material diverter;

[0045] 13-sintering hanger;

[0046] 14-sintering furnace shell;

[0047] 15- heating body;

[0048] 16-graphite insulation barrel;

[0049] 17-metal furnace core tube;

[0050] 18-quartz furnace core tube;

[0051] 19-pressure relief valve;

[0052] 20-pressure gauge;

[0053] 21- Temperature sensor;

[0054] 22-air inlet;

[0055] 23- Partition plate. DETAILED DESCRIPTION

[0056] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0057] The present invention provides high-purity quartz glass for radiation resistance, which includes hydroxyl groups. The mass content of hydroxyl groups in the high-purity quartz glass for radiation resistance is greater than or equal to 300 ppm, the fluctuation of the mass content of hydroxyl groups in the axial direction of the high-purity quartz glass for radiation resistance does not exceed 15 ppm, and the fluctuation of the mass content of hydroxyl groups in the radial direction of the high-purity quartz glass for radiation resistance does not exceed 15 ppm.

[0058] The axial direction of the high-purity quartz glass for radiation resistance in the embodiment of the present invention refers to the direction of the central axis of rotation of the high-purity quartz glass for radiation resistance, that is, the direction common to the central axis of the high-purity quartz glass for radiation resistance; the radial direction of the high-purity quartz glass for radiation resistance in the embodiment of the present invention refers to the direction perpendicular to the axial direction. Exemplarily, when the high-purity quartz glass for radiation resistance is in the shape of a cylinder, the axial direction of the high-purity quartz glass for radiation resistance is the direction common to the central axis, and the radial direction refers to the radius or diameter direction of the end face circle.

[0059] The mass content of hydroxyl in the radiation-resistant high-purity quartz glass of the embodiment of the present invention is greater than or equal to 300 ppm, for example, 300 ppm, 350 ppm, 400 ppm, 500 ppm, 800 ppm, 1000 ppm, 1200 ppm, 1400 ppm or a range consisting of any two thereof.

[0060] In some embodiments, the mass content of hydroxyl in the radiation-resistant high-purity quartz glass is 300-1400 ppm.

[0061] The fluctuation of the mass content of hydroxyl groups in the axial direction of the high-purity quartz glass for radiation resistance of the embodiment of the present invention does not exceed 15 ppm, for example, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14 or 15 ppm. The fluctuation of the mass content of hydroxyl groups in the axial direction of the high-purity quartz glass for radiation resistance of the embodiment of the present invention refers to the difference between the maximum value and the minimum value of the mass content of hydroxyl groups in the axial direction of the high-purity quartz glass for radiation resistance.

[0062] The fluctuation of the mass content of hydroxyl groups in the radial direction of the high-purity quartz glass for radiation resistance of the embodiment of the present invention does not exceed 15 ppm, for example, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14 or 15 ppm. The fluctuation of the mass content of hydroxyl groups in the radial direction of the high-purity quartz glass for radiation resistance of the embodiment of the present invention refers to the difference between the maximum value and the minimum value of the mass content of hydroxyl groups in the radial direction of the high-purity quartz glass for radiation resistance.

[0063] Theoretically, quartz glass should be a complete Si-O network tetrahedron, where each Si atom is connected to four O atoms, and each O atom is connected to two Si atoms, thus forming a three-dimensional silicon-oxygen tetrahedron. This structure includes bond length d(Si-O), with an average of about 1.62A, tetrahedral angle Φ(Si-O-Si), with an average bond angle of about 109°; inter-tetrahedral angle α(Si-O-Si), with an average bond angle of about 144°-150°, ranging from 120° to 180°; and bond torsion angles δ1 and δ2, etc. The continuous change and distortion of the bond angles between Si-O-Si leads to the long-range disordered structural characteristics of quartz optical fiber materials. In the actual quartz [SiO4] tetrahedral network structure, there are a large number of inherent defects, including oxygen-deficient defects (≡Si-O, ≡Si-Si≡) and peroxygen defects (≡Si-O, ≡Si-OO, ≡Si-OO-Si≡). When the quartz glass is subjected to radiation, the structural defects in the quartz glass structure will capture the electrons and holes generated by the radiation to form color center defects. This color center defect will cause absorption in a specific band (especially ultraviolet and visible light fluctuations), resulting in increased attenuation of the quartz glass and causing the quartz glass to have poor signal transmission performance.

[0064] Through the above scheme, the present invention uses the high-purity quartz glass for radiation resistance in optical fibers, which can reduce the attenuation of optical fibers and improve the radiation resistance of optical fibers. The inventor believes that the reason may be that the high-purity quartz glass for radiation resistance contains 300-1400 ppm of hydroxyl groups in its structure, which can form Si-OH, thereby inhibiting the generation of color center defects and thus improving the radiation resistance of the high-purity quartz glass for radiation resistance; and the hydroxyl groups in the high-purity quartz glass for radiation resistance are evenly distributed, which can ensure the uniformity of the silicon dioxide network structure, avoid the generation of deformed structures, reduce the structural stress of the glass, and thus improve the radiation resistance of the high-purity quartz glass for radiation resistance.

[0065] Specifically, the embodiment of the present invention can test the mass percentage of hydroxyl in high-purity quartz glass for radiation resistance through the following steps: select dozens of points (for example, 20 points, 30 points) in the high-purity quartz glass for radiation resistance, test the hydroxyl content of these dozens of points by Fourier infrared, and then take the average value, wherein each point corresponds to a hydroxyl content value, if the hydroxyl content values ​​corresponding to each point in the axial or radial direction are relatively close, it means that the distribution uniformity of hydroxyl in this direction is good; otherwise, vice versa.

[0066] The embodiment of the present invention can test the fluctuation of the axial hydroxyl mass content in the high-purity quartz glass for radiation resistance through the following steps: using a Fourier infrared tester, uniformly testing n points (n≥6) along the axial position, recording the hydroxyl mass content at each position, and calculating the difference between the maximum value and the minimum value, which is the fluctuation of the axial hydroxyl mass content in the high-purity quartz glass for radiation resistance. Exemplarily, 6 to 8 points can be tested to calculate the fluctuation of the axial hydroxyl mass content in the high-purity quartz glass for radiation resistance.

[0067] The embodiment of the present invention can test the fluctuation of the radial hydroxyl mass content in the high-purity quartz glass for radiation resistance through the following steps: using a Fourier infrared tester, uniformly testing n points (n≥3) along the radial position, recording the hydroxyl mass content at each position, and calculating the difference between the maximum value and the minimum value, which is the fluctuation of the radial hydroxyl mass content in the high-purity quartz glass for radiation resistance. Exemplarily, three points can be tested to calculate the fluctuation of the radial hydroxyl mass content in the high-purity quartz glass for radiation resistance.

[0068] In a specific embodiment, the content of impurities in the high-purity quartz glass for radiation resistance is less than 1 ppb, and the optical uniformity of the high-purity quartz glass for radiation resistance is 1-5 ppm, for example, 1 ppm, 1.5 ppm, 2 ppm, 2.5 ppm, 3 ppm, 3.5 ppm, 4 ppm, 4.5 ppm or 5 ppm, etc. When the purity and optical uniformity of the high-purity quartz glass for radiation resistance are respectively within the above ranges, there are few defects in the glass structure, and the impurity atoms are prevented from filling the network structure to cause the network structure deformity defects, which easily cause color centers during radiation, thereby improving the radiation resistance, and at the same time, it can avoid the uneven network structure, for example, avoiding the change of the angle formed by the Si-O bond, resulting in deformity, the existence of stress, and the easy bond breaking and color center during radiation, thereby avoiding the decline of the radiation resistance.

[0069] Specifically, the purity of the radiation-resistant high-purity quartz glass in the embodiment of the present invention is tested by an atomic absorption spectrometer.

[0070] The method for testing the optical uniformity of the high-purity quartz glass for radiation resistance according to the embodiment of the present invention comprises the following steps: testing the cross section of the high-purity quartz glass for radiation resistance by means of a laser interferometer, and calculating the difference between the maximum value and the minimum value of the light transmission intensity in the measured range, which is the optical uniformity of the high-purity quartz glass for radiation resistance.

[0071] The present invention also provides a method for preparing high-purity quartz glass for radiation resistance, comprising the following steps: 1) subjecting a mixed gas of SiCl4, O2, H2, and Ar to a flame hydrolysis reaction under a negative pressure of 20-35 Pa to obtain a silicon dioxide deposit; 2) subjecting the silicon dioxide deposit to a pretreatment, a vitrification treatment, and a purification treatment in sequence to obtain high-purity quartz glass for radiation resistance.

[0072] Specifically, in step 1), at a negative pressure of 20-35Pa, for example, negative pressure 20Pa, negative pressure 21Pa, negative pressure 22Pa, negative pressure 23Pa, negative pressure 24Pa, negative pressure 25Pa, negative pressure 26Pa, negative pressure 27Pa, negative pressure 28Pa, negative pressure 29Pa, negative pressure 30Pa, negative pressure 31Pa, negative pressure 32Pa, negative pressure 33Pa, negative pressure 34Pa or negative pressure 35Pa, a mixed gas of SiCl4, O2, H2 and Ar is subjected to flame hydrolysis reaction to obtain silicon dioxide, which is gradually deposited to obtain a silicon dioxide deposit.

[0073] The chemical reaction formulas of the flame hydrolysis reaction of the embodiment of the present invention are shown in Formula 1 and Formula 2:

[0074] 2H2+O2→2H2O Formula 1

[0075] SiCl4+2H2O→SiO2+4HCl Formula 2.

[0076] Step 2), the silicon dioxide deposit is sequentially subjected to pretreatment, vitrification treatment and purification treatment to obtain high-purity quartz glass for radiation resistance.

[0077] The present invention first prepares a silica deposit, then forms hydroxyl groups in the silica deposit by pretreatment, vitrification treatment and purification treatment, and makes the hydroxyl groups evenly distributed in the silica deposit, thereby improving the radiation resistance of quartz glass and improving the performance of optical fiber. In addition, the preparation method has simple process, easy operation and low energy consumption, which helps to reduce the preparation cost of high-purity quartz glass for radiation resistance and is conducive to expanding the industrial production of high-purity quartz glass for radiation resistance.

[0078] In one embodiment, the length of the silicon dioxide deposit is 900-1500 mm, for example, 900, 1000, 1100, 1200, 1300, 1400 or 1500 mm. Figure 1As shown, the shape of the silica deposit body of the embodiment of the present invention is a cylinder, and the end of the cylinder is in an arc shape. The diameter 2R of the silica deposit body is 100-300 mm, for example, 100 mm, 120 mm, 140 mm, 160 mm, 180 mm, 200 mm, 220 mm, 240 mm, 260 mm, 280 mm or 300 mm, and the ratio of the distance h between the diameter change point and the end of the silica deposit body to the radius R of the silica deposit body (h:R) is 0.1-0.8, for example, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7 or 0.8, etc. When the length of the silica deposit and h:R are within the above range, the silica deposit can form a high content of hydroxyl groups inside through pretreatment, vitrification treatment and purification treatment, and the hydroxyl content in the silica deposit is evenly distributed, and the bottom of the silica deposit is flatter, so that the thermal stress and shrinkage difference between the inner and outer ends in the radial region of the silica deposit is smaller, so that the self-defects in the radiation-resistant high-purity quartz glass are less, and the optical uniformity of the prepared radiation-resistant high-purity quartz glass is better, and the radiation resistance of the radiation-resistant high-purity quartz glass is improved. On the contrary, if the bottom of the silica deposit is conical, the inner radial residual stress of the radiation-resistant high-purity quartz glass after sintering is large, resulting in more self-defects of the radiation-resistant high-purity quartz glass, reducing the optical uniformity of the radiation-resistant high-purity quartz glass.

[0079] In a specific embodiment, step 1) includes the following steps: under a negative pressure of 20-35Pa, a mixed gas of SiCl4, O2, H2, and Ar is subjected to a flame hydrolysis reaction through a blowtorch to deposit silicon dioxide on a target rod to obtain a silicon dioxide deposit; the angle θ between the axis of the blowtorch and the axis of the target rod is 30-50°, the distance L1 between the port of the blowtorch and the axis of the target rod is 80-180mm, and the vertical distance between the port of the blowtorch and the axis of the target rod is L2, L2:L1=0.5-0.76.

[0080] Specifically, under a negative pressure of 20-35 Pa, a mixed gas of SiCl4, O2, H2, and Ar is passed through a blowtorch to undergo a flame hydrolysis reaction to generate silicon dioxide, which is deposited on a target rod to obtain a silicon dioxide deposit; Figure 2As shown, the angle θ between the axis of the blowtorch and the axis of the target rod is 30-50°, for example, 30°, 32°, 34°, 36°, 38°, 40°, 42°, 44°, 46°, 48° or 50°, the distance L1 between the port of the blowtorch and the axis of the target rod is 80-180 mm, for example, 80 mm, 90 mm, 100 mm, 110 mm, 120 mm, 130 mm, 140 mm, 150 mm, 160 mm, 170 mm or 180 mm, and the vertical distance between the port of the blowtorch and the axis of the target rod is L2, L2:L1=0.5-0.76, for example, 0.5, 0.55, 0.6, 0.65, 0.7 or 0.76, etc.

[0081] The embodiment of the present invention controls the angle and spacing relationship between the blowtorch and the target rod, so that the diameter h of the silica deposit body is within the above range, so that the bottom of the silica deposit body is flat, the difference in thermal stress and shrinkage between the inner and outer ends in the radial region is small, and the defects in the high-purity quartz glass for radiation resistance are reduced, thereby improving the radiation resistance of the high-purity quartz glass for radiation resistance.

[0082] In a specific embodiment, the rotation speed of the target rod is 10-40 rpm, for example, 10 rpm, 15 rpm, 20 rpm, 25 rpm, 30 rpm, 35 rpm or 40 rpm, and the deposition rate of silicon dioxide is 0.3-1.5 mm / min, for example, 0.3 mm / min, 0.4 mm / min, 0.5 mm / min, 0.6 mm / min, 0.7 mm / min, 0.8 mm / min, 0.9 mm / min, 1 mm / min, 1.1 mm / min, 1.2 mm / min in, 1.3mm / min, 1.4mm / min or 1.5mm / min, etc.; the flow ratio of SiCl4 to O2 is (1-2):(2-1), for example, 1:2, 1:1.5, 1:1, 1.5:1 or 2:1, etc., the flow ratio of H2 to O2 is (1-3):1, for example, 1:1, 1.5:1, 2:1, 2.5:1 or 3:1, etc., and the flow rate of SiCl4 is 20-40g / min, for example, 20g / min, 25g / min, 30g / min, 35g / min or 40g / min, etc. The embodiment of the present invention can ensure that the axial direction of the silicon dioxide deposit body is uniform when the rod length increases by controlling the rotation speed of the target rod, the deposition rate of silicon dioxide, and the flow rate of the raw material gas, thereby eliminating the difference in contraction force caused by the axial dimension fluctuation of the silicon dioxide deposit body during the vitrification process, thereby reducing the inherent defects in the high-purity quartz glass for radiation resistance, reducing the color center defects after radiation, and improving the radiation resistance of the high-purity quartz glass for radiation resistance.

[0083] In a specific embodiment, the pretreatment includes the following steps: 1) rotating the silica deposit at a rotation speed of 3-6rpm under a negative pressure of 0.2-0.5bar for 1-3h; 2) introducing a water mist with a flow rate of 1000-3000mL / h into the space where the silica deposit is set at 200-400°C and 8-15Pa for 4-8h; wherein the particle size of the water mist is 3-10μm; 3) introducing a water mist with a flow rate of 1000-3000mL / h and an O2 with a flow rate of 2-6L / min at 300-600°C and 10-30Pa for 12-24h to obtain a first intermediate.

[0084] Specifically, in step 1), the silicon dioxide deposit is rotated at a speed of 3-6 rpm, for example, 3 rpm, 3.5 rpm, 4 rpm, 4.5 rpm, 5 rpm, 5.5 rpm or 6 rpm, and vacuum treatment is performed until the negative pressure is 0.2-0.5 bar, for example, 0.2 bar, 0.25 bar, 0.3 bar, 0.35 bar, 0.4 bar, 0.45 bar or 0.5 bar, and the vacuum pressure is maintained for 1.3 hours;

[0085] Step 2), heating to 200-400°C, for example, 200°C, 220°C, 240°C, 260°C, 280°C, 300°C, 320°C, 340°C, 360°C, 380°C or 400°C, etc., pressure 8-15Pa, for example, 8Pa, 9Pa, 10Pa, 11Pa, 12Pa, 13Pa, 14Pa or 15Pa, etc., passing 1000-3000mL / h of water mist, for example, 1000mL / h, 1200mL / h, 1400mL / h, 1600mL / h, 1800mL / h, 2000mL / h, 2200mL / h, 2400mL / h, 2600mL / h, 2800mL / h or 3000mL / h, etc., and maintaining for 4-8h, for example, 4, 5, 6, 7 or 8h, etc.;

[0086] Step 3), the temperature is raised to 300-600°C, for example, 300°C, 350°C, 400°C, 450°C, 500°C, 550°C or 600°C, the pressure is 10-30Pa, for example, 10Pa, 15Pa, 20Pa, 25Pa or 30Pa, and 1000-3000mL / h of water mist is introduced, for example, 1000mL / h, 1200mL / h, 1400mL / h, 1600mL / h, 1800mL / h, etc. 00mL / h, 2000mL / h, 2200mL / h, 2400mL / h, 2600mL / h, 2800mL / h or 3000mL / h, and 2-6L / min of O2, for example 2L / min, 3L / min, 4L / min, 5L / min or 6L / min, etc., maintained for 12-24h, for example 12, 14, 16, 18, 20, 22 or 24, etc., to obtain a first intermediate.

[0087] like Figure 3 As shown, the pretreatment of the embodiment of the present invention includes three stages, namely, vacuuming at room temperature, passing water at low temperature, and passing oxygen at low temperature, which can remove the air in the gaps of the silicon dioxide deposit and promote the migration of water molecules and oxygen molecules under high pressure, thereby forming a water-rich film or an oxygen-rich film on the surface of the silicon dioxide particles, providing a basis for the subsequent formation of a high content of hydroxyl groups in the high-purity quartz glass for radiation resistance.

[0088] In one embodiment, the vitrification process comprises the following steps:

[0089] At 1300-1500° C., for example, 1300, 1350, 1400, 1450 or 1500° C., water mist with a flow rate of 1000-3000 mL / h, for example, 1000 mL / h, 1200 mL / h, 1400 mL / h, 1600 mL / h, 1800 mL / h, 2000 mL / h, 2200 mL / h, 2400 mL / h, 2600 mL / h, 2800 mL / h, etc., is introduced into the space where the first intermediate is arranged. mL / h or 3000mL / h, etc., O2 with a flow rate of 2-6L / min, for example, 2L / min, 3L / min, 4L / min, 5L / min or 6L / min, etc., He with a flow rate of 8-25L / min, for example, 8L / min, 10L / min, 15L / min, 20L / min or 25L / min, etc., maintain 4-6h, for example, 4h, 4.5h, 5h, 5.5h or 6h, etc., to obtain a second intermediate.

[0090] like Figure 3As shown, the vitrification treatment of the embodiment of the present invention is carried out at a high temperature, which can open the Si-O network structure in the radiation-resistant high-purity quartz glass, thereby forming a radiation-resistant high-purity quartz glass with an oxygen-rich Si-OO-Si or Si-OH structure, and the amount of water mist introduced is controlled, so that the mass content of hydroxyl groups in the radiation-resistant high-purity quartz glass is high, which is beneficial to improve the radiation resistance of the radiation-resistant high-purity quartz glass.

[0091] The chemical reaction formulas in the vitrification process of the embodiment of the present invention are shown in Formula 3 and Formula 4:

[0092] ≡Si-O-Si≡+H2O→≡2Si-OH Formula 3

[0093] ≡Si-O-Si≡+O2→≡Si-OO-Si≡Equation 4.

[0094] In one embodiment, the particle size of water in the water mist of the embodiment of the present invention is 3-10 μm, for example, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm.

[0095] In a specific embodiment, the purification treatment includes the following steps: cooling the second intermediate to less than 100° C. for 30-60 min, such as 30 min, 35 min, 40 min, 45 min, 50 min, 55 min or 60 min; after the second intermediate is cooled, at a negative pressure of 0.3-0.6 bar, such as negative pressure 0.3 bar, negative pressure 0.35 bar, negative pressure 0.4 bar, negative pressure 0.45 bar, negative pressure 0.5 bar, negative pressure 0.5 5bar or negative pressure 0.6bar, etc., into the space where the second intermediate is set, a mixture of H2 and Ar with a flow rate of 3-5L / min and a flow rate of He of 3-5L / min, for example, 3L / min, 3.2L / min, 3.4L / min, 3.6L / min, 3.8L / min, 4L / min, 4.2L / min, 4.4L / min, 4.6L / min, 4.8L / min or 5L / min, etc., until the pressure of the space is a positive pressure of 0.5-2 bar, for example, 0.5 bar, 0.6 bar, 0.7 bar, 0.8 bar, 0.9 bar, 1 bar, 1.1 bar, 1.2 bar, 1.3 bar, 1.4 bar, 1.5 bar, 1.6 bar, 1.7 bar, 1.8 bar, 1.9 bar or 2 bar, etc., the temperature is increased to 400-800 ° C, for example, 400 ° C, 450 ° C, 500 ° C, 600 ° C, 650 ° C, 700 ° C, 750 ° C or 800 ° C, etc., the heating rate 10-20°C / min, for example, 10°C / min, 11°C / min, 12°C / min, 13°C / min, 14°C / min, 15°C / min, 16°C / min, 17°C / min, 18°C / min, 19°C / min or 20°C / min, etc., constant temperature and pressure for 60-150h, for example, 60h, 70h, 80h, 90h, 100h, 110h, 120h, 130h, 140h, 150h, etc., to obtain high-purity quartz glass for radiation resistance;

[0096] Among them, the volume proportion of H2 in the H2 and Ar mixed gas is 1-3%, for example, 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, 2.2%, 2.4%, 2.6%, 2.8% or 3%.

[0097] like Figure 3 As shown, the purification process of the embodiment of the present invention first undergoes a forced cooling process, and uses stress to drive the Si-O-Si or Si-OO-Si structure in the radiation-resistant high-purity quartz glass to break, forming non-bridging oxygen vacancy centers NBOHCs (≡Si-OO ·, ≡Si-O··O-Si) structure, then introduce H2 and He mixed gas, so that hydrogen molecules penetrate into the glass under high temperature and pressure, reduce and repair NBOHCs, and form Si-OH and other structures. He has good heat transfer function, which helps to make the temperature inside and outside of high-purity quartz glass for radiation resistance uniform, so that hydrogen molecules diffuse into high-purity quartz glass for radiation resistance faster and form hydroxyl structure. At the same time, this process is also a good glass structure relaxation stage, which effectively releases internal stress and eliminates glass micro defects, thereby better improving the radiation resistance of high-purity quartz glass for radiation resistance.

[0098] The chemical reaction formulas in the purification process of the embodiment of the present invention are shown in Formula 5, Formula 6, and Formula 7:

[0099] ≡Si-OO · +H2→≡Si-OO-H+H + Formula 5

[0100] ≡Si-OO-Si≡+H2→≡2Si-OH Formula 6

[0101] ≡Si-O··O-Si≡+H2→≡2Si-OH Formula 7.

[0102] The present invention also provides a device, which includes a flame hydrolysis reaction unit, a pretreatment unit, a vitrification treatment unit and a purification treatment unit; the flame hydrolysis reaction unit is used for flame hydrolysis reaction; the pretreatment unit is used for pretreatment; the vitrification treatment unit is used for vitrification treatment; and the purification treatment unit is used for purification treatment.

[0103] In a specific embodiment, the flame hydrolysis reaction unit of the embodiment of the present invention includes a deposition device, such as Figure 4 As shown, the deposition equipment is provided with a blowtorch 1, an air supply system 2, a pressure control console 3, an exhaust system 4, a deposition boom 5, a pressure detector 6, a target rod 7, a silica deposition body 8, a deposition chamber 9, a CCD camera 10, a silica deposition body imaging diameter measurement system 11, and a raw material diverter 12.

[0104] The blowtorch is used to mix the gas for flame hydrolysis reaction. The deposition boom can be rotated so that the silicon dioxide deposition body can be rotated. The target rod is used to deposit silicon dioxide to form a silicon dioxide deposition body.

[0105] The adjustable angle θ between the burner axis and the target rod axis is 30-50°, the distance L1 between the burner port and the target rod axis is 80-180 mm, and the vertical distance between the burner port and the target rod axis is L2, L2: L1 = 0.5-0.76.

[0106] The air supply system is composed of a high-efficiency filter (filtering particle size above 0.5um) and an automatic air supply structure, and the exhaust system is equipped with an automatic air supply structure. By collecting the pressure monitor value and the opening and closing signals of the air supply / exhaust valve to the PLC online monitoring integrated platform, and adjusting the opening and closing of the air supply system and the exhaust system, the pressure and airflow in the deposition chamber are stabilized, and the volume change of the deposition equipment as the length of the silica deposit increases, which causes airflow fluctuations, is avoided, thereby ensuring the uniform axial rod diameter of the silica deposit.

[0107] The CCD camera diameter measurement system mainly uses a CCD camera to online monitor the end shape of the silica deposit, and calculates the diameter 2R of the silica deposit and the distance h between the diameter change point and the end of the silica deposit through software.

[0108] In one embodiment, the pretreatment unit, the vitrification unit and the purification unit include a sintering furnace, such as Figure 5 As shown, the sintering furnace is divided into two chambers, upper and lower.

[0109] The upper chamber of the sintering furnace of the embodiment of the present invention adopts a metal shell, graphite heating, a graphite insulation barrel and a corrosion-resistant and high-temperature metal inner layer (titanium alloy, nickel alloy, etc.). The lower chamber is composed of a shell, a graphite heating body, a graphite insulation barrel and a quartz barrel. The heating zone lengths of the upper and lower chambers are the same, which meets 1.3 to 1.6 times of the powder rod, preferably 1.5 times. The upper and lower chambers are equipped with independent temperature control systems, pressure sensor systems and pressure relief valves to monitor the temperature and pressure in the furnace in real time. At the same time, the furnace body of the upper and lower chambers is evenly distributed with three gas inlets in the longitudinal direction, preferably in a cross arrangement (the number of inlets here is not limited, it can be more, the purpose is to evenly pass the gas into the furnace). A multi-layer high-temperature resistant material partition plate (metal + graphite + quartz) is used between the upper and lower chambers, and is formed by merging two semicircles, which can be stretched outwards respectively to achieve opening and closing.

[0110] also, Figure 5 It can be seen that the sintering furnace shell is on the outer layer of the sintering furnace. The sintering furnace may also include a metal furnace core tube, a quartz furnace core tube, a pressure gauge, a temperature sensor, an air inlet, and a sintering hanger.

[0111] The pretreatment of the embodiment of the present invention is carried out in the upper chamber. After the pretreatment is completed, the first intermediate is lowered into the lower chamber for vitrification treatment. After the vitrification treatment is completed, the second intermediate is lifted up into the upper chamber for passivation treatment to obtain high-purity quartz glass for radiation resistance.

[0112] The device provided by the present invention has a simple composition and low cost, can save the equipment cost for preparing high-purity quartz glass for radiation resistance, and lays a foundation for the industrialized production of high-purity quartz glass for radiation resistance.

[0113] The present invention also provides an optical fiber, which is made of the above-mentioned high-purity quartz glass for radiation resistance and has high radiation resistance.

[0114] In a specific embodiment, the method for preparing an optical fiber comprises the following steps: drawing radiation-resistant high-purity quartz glass into an optical fiber core at a high temperature, and then matching a low-refractive-index cladding outside the optical fiber core to obtain an optical fiber.

[0115] The embodiment of the present invention does not limit the drawing temperature of the radiation-resistant high-purity quartz glass, as long as the radiation-resistant high-purity quartz glass can be drawn into an optical fiber core, and the temperature can be selected according to actual needs.

[0116] The low refractive index cladding in the embodiment of the present invention includes fluorine-doped quartz glass and low refractive index resin (such as polystyrene, polycarbonate, polymethyl methacrylate).

[0117] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0118] The present invention is further described below by specific examples and comparative examples. Unless otherwise specified, the reagents, materials and instruments used below are all conventional reagents, conventional materials and conventional instruments, which can be commercially available, and the reagents and materials involved can also be synthesized by conventional synthesis methods.

[0119] Example 1

[0120] The method for preparing the diaphragm of this embodiment comprises the following steps:

[0121] 1. Preparation of silica deposit: SiCl4, O2, H2, and Ar are introduced into the blowtorch, and the flame hydrolysis reaction produces SiO2 particles that are accumulated on the target rod, and the deposition is gradually lifted until the target rod is 1000mm long. During the deposition process, the rotation speed is 10rpm and the lifting speed is 0.3mm / min. The SiCl4 flow rate is 20g / min, the O2 flow rate is 40L / min, and the H2 flow rate is 120L / min. The deposition equipment is equipped with a blowtorch, an air supply system, an exhaust system, a pressure monitor, and a CCD camera diameter measurement system. The adjustable angle θ between the blowtorch axis and the target rod axis is 50°, the distance L1 between the blowtorch port and the target rod axis is 80mm, and the vertical distance between the blowtorch port and the target rod axis is L2, L2: L1 = 0.76. The air supply system consists of a high-efficiency filter (filtering particle size above 0.5um) and an automatic air supply structure, and the exhaust system is equipped with an automatic air supply structure. During the deposition process, the pressure controls the negative pressure state and stabilizes at 20Pa. By collecting the pressure monitor value and the opening / closing degree signals of the air supply / exhaust valve to the PLC online monitoring integrated platform, and adjusting the opening and closing degree of the air supply system and the exhaust system, the pressure and airflow in the deposition chamber are stabilized, and the axial distribution of the silica deposit is 120±3mm. The CCD camera diameter measurement system mainly uses the CCD camera to realize online monitoring of the shape of the powder rod end, and calculates the diameter 2R of the silica deposit and the distance h between the diameter change point and the end of the silica deposit through software, and obtains h:R=0.75.

[0122] 2. Sintering of silica deposits: The sintering furnace is divided into two chambers, upper and lower. The upper chamber uses a metal shell, graphite heating, graphite insulation barrel and a corrosion-resistant and high-temperature resistant metal inner layer (titanium alloy). The lower chamber consists of a shell, a graphite heating body, a graphite insulation barrel and a quartz barrel. The heating zone length of the upper and lower chambers is the same, which is 1300mm. The furnace body of the upper and lower chambers has three gas inlets evenly distributed along the longitudinal direction, arranged in a cross manner.

[0123] The sintering process is divided into three steps as follows:

[0124] ① Pretreatment stage: A. Fix the powder rod on the suspension rod and place it in the upper chamber of the sintering furnace. The suspension rod rotates at 3rpm and vacuum is applied at room temperature with a negative pressure of 0.2bar for 3h.

[0125] B. Rapidly raise the temperature to 200°C, introduce water mist at a flow rate of 3000ml / h, maintain a positive pressure of 8pa, and keep the temperature constant for 6h;

[0126] C. Then quickly raise the temperature to 600°C, maintain the water mist flow rate at 3000ml / h, the O2 flow rate at 6L / min, maintain the positive pressure at 30Pa in the furnace, and maintain the constant temperature for 24h to obtain the first intermediate.

[0127] ②Vitrification stage: Open the middle isolation plate, and further lower the first intermediate into the lower chamber. The rotation speed of the suspension rod remains unchanged, the furnace temperature is 1300℃, and the temperature is constant for 6 hours. The furnace maintains a positive pressure of 30Pa, and O2, water mist, and He are introduced simultaneously to form a transparent glass rod. The O2 flow rate is 6L / min, the water mist flow rate is 3000ml / h, and the He flow rate is 8L / min. After the end, the furnace temperature is depressurized, and the introduction of oxygen, water mist, and He is stopped. When the pressure in the furnace is equal to the external environmental pressure, close the pressure relief valve, and the second intermediate.

[0128] ③ Purification stage: Raise the second intermediate to the upper chamber, keep the rotation speed of the boom unchanged, close the isolation plate at the same time, turn on N2 to force cooling to less than 100°C, and control the cooling time to 30 minutes. After cooling, evacuate to a negative pressure of 0.6 bar. Then, introduce a H2 and Ar mixed gas with a flow rate of 5L / min, where the H2 concentration is 1% and the He flow rate is 5L / min. The positive pressure of the furnace is controlled at 2bar, and the temperature is raised to 800°C at a heating rate of 20°C / min. Maintain constant temperature and pressure for 60 hours to allow hydrogen to diffuse in high-purity quartz glass for radiation resistance.

[0129] The radiation-resistant high-purity quartz glass prepared above was tested uniformly along the axial direction and the radial position of each axial cross section by a Fourier infrared tester, and the hydroxyl content thereof reached 1400ppm±15ppm.

[0130] The results of atomic absorption spectrometer tests showed that the impurity content in the high-purity quartz glass for radiation resistance is less than 1 ppb.

[0131] The optical uniformity was tested by laser interferometer and was found to be 4.6ppm.

[0132] The quartz rod is matched with fluorine-doped high-purity quartz glass for radiation resistance as a low-refractive index cladding to prepare an optical fiber preform rod, and then the optical fiber is drawn at high temperature. The optical fiber is then subjected to radiation treatment (total dose of 10KGy, 300Gy / h dose), and the typical attenuation values ​​of the optical fiber at 1310nm and 1550nm after radiation are 18.3dB / km and 16.6dB / km.

[0133] Embodiment 2:

[0134] The method for preparing the diaphragm of this embodiment comprises the following steps:

[0135] 1. Preparation of silica deposit: SiCl4, O2, H2, and Ar are introduced into the blowtorch, and the flame hydrolysis reaction produces SiO2 particles that are accumulated on the target rod, and the deposition is gradually lifted until the target rod is 1200mm long. During the deposition process, the rotation speed is 25rpm and the lifting speed is 1.0mm / min. The SiCl4 flow rate is 30g / min, the O2 flow rate is 15L / min, and the H2 flow rate is 45L / min. The deposition equipment is equipped with a blowtorch, an air supply system, an exhaust system, a pressure monitor, and a CCD camera diameter measurement system. The adjustable angle θ between the blowtorch axis and the target rod axis is 45°, the distance L1 between the blowtorch port and the target rod axis is 130mm, and the vertical distance between the blowtorch port and the target rod axis is L2, L2: L1 = 0.71. The air supply system consists of a high-efficiency filter (filtering particle size above 0.5um) and an automatic air supply structure, and the exhaust system is equipped with an automatic air supply structure. During the deposition process, the pressure controls the negative pressure state and stabilizes at 30Pa. By collecting the pressure monitor value and the opening / closing degree signals of the air supply / exhaust valve to the PLC online monitoring integrated platform, the pressure and airflow of the deposition chamber are stabilized by adjusting the opening and closing degree of the air supply system and the exhaust system, and the axial distribution of the silica deposit is 133±2.5mm. The CCD camera diameter measurement system mainly uses the CCD camera to realize online monitoring of the shape of the powder rod end, and calculates the diameter 2R of the silica deposit and the distance h between the diameter change point and the end of the silica deposit through software, and obtains h:R=0.75.

[0136] 2. Sintering of silica deposits: The sintering furnace is divided into two chambers, upper and lower. The upper chamber uses a metal shell, graphite heating, graphite insulation barrel and a corrosion-resistant and high-temperature resistant metal inner layer (titanium alloy). The lower chamber consists of a shell, a graphite heating body, a graphite insulation barrel and a quartz barrel. The heating zone length of the upper and lower chambers is the same, which is 1800mm. The furnace body of the upper and lower chambers has three gas inlets evenly distributed along the longitudinal direction, arranged in a cross manner.

[0137] The sintering process is divided into three steps as follows:

[0138] ① Pretreatment stage: A. Fix the powder rod on the suspension rod and place it in the upper chamber of the sintering furnace. The suspension rod rotates at 4.5rpm and vacuum is applied at room temperature with a negative pressure of 0.3bar for 2h.

[0139] B. Rapidly raise the temperature to 300°C, introduce water mist at a flow rate of 2000ml / h, maintain a positive pressure of 12pa, and keep the temperature constant for 8h;

[0140] C. Then quickly raise the temperature to 450°C, keep the water mist flow rate at 2000ml / h, the O2 flow rate at 4L / min, maintain the positive pressure at 20Pa in the furnace, and keep the temperature constant for 18h to obtain the first intermediate.

[0141] ②Vitrification stage: Open the middle isolation plate, and further lower the first intermediate into the lower chamber. The rotation speed of the suspension rod remains unchanged, the furnace temperature is 1400℃, and the temperature is constant for 5 hours. The positive pressure in the furnace is maintained at 20Pa, and O2, water mist, and He are introduced simultaneously to form a transparent glass rod. The O2 flow rate is 4L / min, the water mist flow rate is 2000ml / h, and the He flow rate is 15L / min. After the end, the furnace temperature is depressurized, and the introduction of oxygen, water mist, and He is stopped. When the pressure in the furnace is equal to the external environmental pressure, the pressure relief valve is closed, and the second intermediate is formed.

[0142] ③ Purification stage: Raise the second intermediate to the upper chamber, keep the rotation speed of the boom unchanged, close the isolation plate at the same time, turn on N2 for forced cooling to less than 100°C, and control the cooling time to 45 minutes. After cooling, evacuate to a negative pressure of 0.4 bar. Then, introduce a H2 and Ar mixed gas with a flow rate of 4L / min, where the H2 concentration is 2% and the He flow rate is 4L / min. The positive pressure of the furnace is controlled at 1.2 bar, and the temperature is raised to 600°C at a heating rate of 15°C / min. Maintain constant temperature and pressure for 100 hours to allow hydrogen to diffuse in the high-purity quartz glass for radiation resistance.

[0143] The radiation-resistant high-purity quartz glass prepared above was tested uniformly along the axial direction and the radial position of each axial cross section by a Fourier infrared tester, and the hydroxyl content thereof reached 1030ppm±10ppm.

[0144] The results of atomic absorption spectrometer tests showed that the impurity content in the high-purity quartz glass for radiation resistance is less than 1 ppb.

[0145] The optical uniformity was tested by laser interferometer and was found to be 3.8ppm.

[0146] The quartz rod is matched with fluorine-doped high-purity quartz glass for radiation resistance as a low refractive index cladding to prepare an optical fiber preform rod, and then the optical fiber is drawn at high temperature. The optical fiber is then subjected to radiation treatment (total dose of 10KGy, 300Gy / h dose), and the typical attenuation values ​​of the optical fiber at 1310nm and 1550nm after radiation are 16.7dB / km and 14.8dB / km.

[0147] Embodiment 3:

[0148] The method for preparing the diaphragm of this embodiment comprises the following steps:

[0149] 1. Preparation of silica deposit: SiCl4, O2, H2, and Ar are introduced into the blowtorch, and the flame hydrolysis reaction produces SiO2 particles that are accumulated on the target rod, and the deposition is gradually lifted until the target rod is 1200mm long. During the deposition process, the rotation speed is 25rpm and the lifting speed is 1.0mm / min. The SiCl4 flow rate is 40g / min, the O2 flow rate is 30L / min, and the H2 flow rate is 80L / min. The deposition equipment is equipped with a blowtorch, an air supply system, an exhaust system, a pressure monitor, and a CCD camera diameter measurement system. The adjustable angle θ between the blowtorch axis and the target rod axis is 30°, the distance L1 between the blowtorch port and the target rod axis is 180mm, and the vertical distance between the blowtorch port and the target rod axis is L2, L2: L1 = 0.50. The air supply system consists of a high-efficiency filter (filtering particle size above 0.5um) and an automatic air supply structure, and the exhaust system is equipped with an automatic air supply structure. During the deposition process, the pressure controls the negative pressure state and stabilizes at 25Pa. By collecting the pressure monitor value and the opening / closing degree signals of the air supply / exhaust valve to the PLC online monitoring integrated platform, the pressure and airflow in the deposition chamber are stabilized by adjusting the opening and closing degree of the air supply system and the exhaust system, and the axial distribution of the silica deposit is 145±3mm. The CCD camera diameter measurement system mainly uses the CCD camera to realize online monitoring of the shape of the powder rod end, and calculates the diameter 2R of the silica deposit and the distance h between the diameter change point and the end of the silica deposit through software, and obtains h:R=0.47.

[0150] 2. Sintering of silica deposits: The sintering furnace is divided into two chambers, upper and lower. The upper chamber uses a metal shell, graphite heating, graphite insulation barrel and a corrosion-resistant and high-temperature resistant metal inner layer (titanium alloy). The lower chamber consists of a shell, a graphite heating body, a graphite insulation barrel and a quartz barrel. The heating zone length of the upper and lower chambers is the same, which is 1800mm. The furnace body of the upper and lower chambers has three gas inlets evenly distributed along the longitudinal direction, arranged in a cross manner.

[0151] The sintering process is divided into three steps as follows:

[0152] ① Pretreatment stage: A. Fix the powder rod on the suspension rod and place it in the upper chamber of the sintering furnace. The suspension rod rotates at 4.5rpm and vacuum is drawn at room temperature with a negative pressure of 0.8bar for 1h.

[0153] B. Rapidly raise the temperature to 300°C, introduce water mist at a flow rate of 2200ml / h, maintain a positive pressure of 12pa, and keep the temperature constant for 6h;

[0154] C. Then keep the temperature at 300°C, keep the water mist flow rate at 2200ml / h, the O2 flow rate at 4L / min, maintain the positive pressure at 18Pa in the furnace, and keep the temperature constant for 20h to obtain the first intermediate.

[0155] ②Vitrification stage: open the middle isolation plate, further lower the first intermediate into the lower chamber, keep the rotation speed of the suspension rod unchanged, keep the furnace temperature at 1400℃, keep the temperature constant for 5h, keep the positive pressure in the furnace at 18Pa, introduce O2, water mist, and He simultaneously to form a transparent glass rod, where the O2 flow rate is 4L / min, the water mist flow rate is 2200ml / h, and the He flow rate is 25L / min. After the end, release the furnace temperature and stop introducing oxygen, water mist, and He. When the pressure in the furnace is equal to the external environment pressure, close the pressure relief valve, and the second intermediate.

[0156] ③ Purification stage: Raise the second intermediate to the upper chamber, keep the rotation speed of the boom unchanged, close the isolation plate at the same time, turn on N2 to force cooling to less than 100°C, and control the cooling time to 40 minutes. After cooling, evacuate to a negative pressure of 0.4 bar. Then, introduce a H2 and Ar mixed gas with a flow rate of 4L / min, where the H2 concentration is 2.2%, the He flow rate is 3.5L / min, the positive pressure of the furnace is controlled at 1 bar, and the temperature is raised to 550°C at a heating rate of 12°C / min. Maintain constant temperature and pressure for 120 hours, so that hydrogen can diffuse in the high-purity quartz glass for radiation resistance.

[0157] The radiation-resistant high-purity quartz glass prepared above was tested uniformly along the axial direction and the radial position of each axial cross section by a Fourier transform infrared tester, and the hydroxyl content thereof reached 850ppm±12ppm.

[0158] The results of atomic absorption spectrometer tests showed that the impurity content in the high-purity quartz glass for radiation resistance is less than 1 ppb.

[0159] The optical uniformity was tested by laser interferometer and was found to be 3.6 ppm.

[0160] The quartz rod is matched with fluorine-doped high-purity quartz glass for radiation resistance as a low-refractive index cladding to prepare an optical fiber preform rod, and then the optical fiber is drawn at high temperature. The optical fiber is then subjected to radiation treatment (total dose of 10KGy, 300Gy / h dose), and the typical attenuation values ​​of the optical fiber at 1310nm and 1550nm after radiation are 16.2dB / km and 14.4dB / km.

[0161] Embodiment 4:

[0162] The method for preparing the diaphragm of this embodiment comprises the following steps:

[0163] 1. Preparation of silica deposit: SiCl4, O2, H2, and Ar are introduced into the blowtorch, and the flame hydrolysis reaction produces SiO2 particles that are accumulated on the target rod, and the deposition is gradually lifted until the target rod is 1500mm long. During the deposition process, the rotation speed is 40rpm and the lifting speed is 1.5mm / min. The SiCl4 flow rate is 40g / min, the O2 flow rate is 20L / min, and the H2 flow rate is 20L / min. The deposition equipment is equipped with a blowtorch, an air supply system, an exhaust system, a pressure monitor, and a CCD camera diameter measurement system. The adjustable angle θ between the blowtorch axis and the target rod axis is 30°, the distance L1 between the blowtorch port and the target rod axis is 150mm, and the vertical distance between the blowtorch port and the target rod axis is L2, L2: L1 = 0.50. The air supply system consists of a high-efficiency filter (filtering particle size above 0.5um) and an automatic air supply structure, and the exhaust system is equipped with an automatic air supply structure. During the deposition process, the pressure controls the negative pressure state and stabilizes at 35Pa. By collecting the pressure monitor value and the opening / closing degree signals of the air supply / exhaust valve to the PLC online monitoring integrated platform, the pressure and airflow of the deposition chamber are stabilized by adjusting the opening and closing degree of the air supply system and the exhaust system, and the axial distribution of the silica deposit is 200±4mm. The CCD camera diameter measurement system mainly uses the CCD camera to realize online monitoring of the shape of the powder rod end, and calculates the diameter 2R of the silica deposit and the distance h between the diameter change point and the end of the silica deposit through software, and obtains h:R=0.42.

[0164] 2. Sintering of silica deposits: The sintering furnace is divided into two chambers, upper and lower. The upper chamber uses a metal shell, graphite heating, graphite insulation barrel and a corrosion-resistant and high-temperature resistant metal inner layer (titanium alloy). The lower chamber consists of a shell, a graphite heating body, a graphite insulation barrel and a quartz barrel. The heating zone length of the upper and lower chambers is the same, which is 2400mm. The furnace body of the upper and lower chambers has three gas inlets evenly distributed along the longitudinal direction, arranged in a cross manner.

[0165] The sintering process is divided into three steps as follows:

[0166] ① Pretreatment stage: A. Fix the powder rod on the suspension rod and place it in the upper chamber of the sintering furnace. The suspension rod rotates at 6rpm and vacuum is drawn at room temperature with a negative pressure of 0.5bar for 2h.

[0167] B. Rapidly raise the temperature to 400°C, introduce water mist with a flow rate of 1000ml / h, maintain a positive pressure of 15pa, and keep the temperature constant for 4h;

[0168] C. Then quickly raise the temperature to 400°C, maintain the water mist flow rate at 1000ml / h, the O2 flow rate at 2L / min, maintain the positive pressure at 10Pa in the furnace, and maintain the constant temperature for 12h to obtain the first intermediate.

[0169] ②Vitrification stage: open the middle isolation plate, further lower the first intermediate into the lower chamber, keep the rotation speed of the suspension rod unchanged, keep the furnace temperature at 1500℃, keep the constant temperature for 4h, keep the positive pressure in the furnace at 10Pa, and introduce O2, water mist, and He simultaneously to form a transparent glass rod, where the O2 flow rate is 2L / min, the water mist flow rate is 1000ml / h, and the He flow rate is 10L / min. After the end, release the furnace temperature and stop introducing oxygen, water mist, and He. When the pressure in the furnace is equal to the external environment pressure, close the pressure relief valve, and the second intermediate.

[0170] ③ Purification stage: Raise the second intermediate to the upper chamber, keep the rotation speed of the boom unchanged, close the isolation plate at the same time, turn on N2 to force cooling to less than 100°C, and control the cooling time to 60min. After cooling, evacuate to a negative pressure of 0.3bar. Then, introduce a H2 and Ar mixed gas with a flow rate of 5L / min, where the H2 concentration is 3% and the He flow rate is 3L / min. The positive pressure of the furnace is controlled at 0.5bar, and the temperature is raised to 400°C at a heating rate of 10°C / min. Maintain constant temperature and pressure for 150h, so that hydrogen can diffuse in the high-purity quartz glass for radiation resistance.

[0171] The radiation-resistant high-purity quartz glass prepared above was tested uniformly along the axial direction and the radial position of each axial cross section by a Fourier infrared tester, and the hydroxyl content thereof reached 800ppm±15ppm.

[0172] The results of atomic absorption spectrometer tests showed that the impurity content in the high-purity quartz glass for radiation resistance is less than 1 ppb.

[0173] The optical uniformity was tested by laser interferometer and was found to be 3.5 ppm.

[0174] The quartz rod is matched with fluorine-doped high-purity quartz glass for radiation resistance as a low-refractive index cladding to prepare an optical fiber preform rod, and then the optical fiber is drawn at high temperature. The optical fiber is then subjected to radiation treatment (total dose of 10KGy, 300Gy / h dose), and the typical attenuation values ​​of the optical fiber at 1310nm and 1550nm after radiation are 17.9dB / km and 16.7dB / km.

[0175] Example 5

[0176] The preparation method of the radiation-resistant high-purity quartz glass in this embodiment is substantially the same as that in Embodiment 1, except that the length of the silicon dioxide deposit is 900 mm, the diameter of the silicon dioxide deposit is 120±3 mm, and h:R=0.77;

[0177] The radiation-resistant high-purity quartz glass prepared above was tested uniformly along the axial direction and the radial position of each axial cross section by a Fourier infrared tester, and the hydroxyl content thereof reached 1400ppm±15ppm.

[0178] The results of atomic absorption spectrometer tests showed that the impurity content in the high-purity quartz glass for radiation resistance is less than 1 ppb.

[0179] The optical uniformity was tested by laser interferometer and was measured to be 4.8ppm.

[0180] The quartz rod is matched with fluorine-doped high-purity quartz glass for radiation resistance as a low-refractive index cladding to prepare an optical fiber preform rod, and then the optical fiber is drawn at high temperature. The optical fiber is then subjected to radiation treatment (total dose of 10KGy, 300Gy / h dose), and the typical attenuation values ​​of the optical fiber at 1310nm and 1550nm after radiation are 18.7dB / km and 16.5dB / km.

[0181] Comparative Example 1:

[0182] 1. Preparation of silica deposit: SiCl4, O2, H2, and Ar are introduced into the blowtorch, and the flame hydrolysis reaction produces SiO2 particles that are accumulated on the target rod, and the deposition is gradually lifted until the target rod is 1000mm long. During the deposition process, the rotation speed is 10rpm and the lifting speed is 0.3mm / min. The SiCl4 flow rate is 20g / min, the O2 flow rate is 40L / min, and the H2 flow rate is 120L / min. The deposition equipment is equipped with a blowtorch, an exhaust system, and a CCD camera diameter measurement system. The adjustable angle θ between the blowtorch axis and the target rod axis is 55°, the distance L1 between the blowtorch port and the target rod axis is 80mm, and the vertical distance between the blowtorch port and the target rod axis is L2, L2: L1 = 0.82. Among them, fixed exhaust is adopted, there is no pressure control, and the pressure changes with the length of the deposition rod. Finally, the rod diameter of the silica deposit gradually changes from 130mm to 108mm, and the axial rod diameter fluctuates to 22mm. The CCD camera diameter measurement system mainly uses a CCD camera to monitor the shape of the powder rod end online, and calculates the diameter 2R of the silica deposit and the distance h between the silica deposit diameter change point and the end through software, and it can be obtained that h:R=1.33.

[0183] 2. Powder rod sintering: The sintering furnace is divided into two chambers, upper and lower. The upper chamber adopts metal shell, graphite heating, graphite insulation barrel and corrosion-resistant and high-temperature resistant metal inner layer (titanium alloy). The lower chamber is composed of shell, graphite heating body, graphite insulation barrel and quartz barrel. The heating zone length of the upper and lower chambers is the same, which is 1300mm, and the gas is introduced from the bottom of the furnace body of the upper and lower chambers.

[0184] The sintering process is divided into three steps as follows:

[0185] ① Pretreatment stage: A. Fix the silica deposit on the suspension rod and place it in the upper chamber of the sintering furnace. The suspension rod rotates at a speed of 3 rpm. Vacuum is drawn at room temperature with a negative pressure of 0.2 bar for 1 hour. B. The temperature is quickly raised to 200°C, and a water mist flow rate of 800 ml / h is introduced. The positive pressure is maintained at 8 pa and the temperature is kept constant for 4 hours. C. Maintain 600°C, the water mist flow rate is maintained at 800 ml / h, the O2 flow rate is 6 L / min, the positive pressure in the furnace is maintained at 30 pa, and the temperature is maintained constant for 24 hours to obtain the first intermediate.

[0186] ②Vitrification stage: Open the middle isolation plate, and further lower the first intermediate into the lower chamber. The rotation speed of the suspension rod remains unchanged, the furnace temperature is 1300℃, and the temperature is constant for 6 hours. The furnace body maintains a positive pressure of 30pa, and O2, water mist, and He are introduced simultaneously to form a transparent glass rod. The O2 flow rate is 6L / min, the water mist flow rate is 800ml / h, and the He flow rate is 8L / min. After the end, the furnace temperature is depressurized, and the introduction of oxygen, water mist, and He is stopped. When the pressure in the furnace is equal to the external environmental pressure, the pressure relief valve is closed to obtain the second intermediate.

[0187] ③ Purification stage: The second intermediate is raised to the upper chamber, the rotation speed of the boom remains unchanged, and the vacuum is directly turned on to a negative pressure of 0.6 bar. Then, a H2 and Ar mixed gas with a flow rate of 5L / min is introduced, where the H2 concentration is 3% and the He flow rate is 5L / min. The positive pressure of the furnace is controlled at 2bar, the temperature is controlled at 800℃, and the temperature and pressure are kept constant for 120h, so that the hydrogen can be diffused in the high-purity quartz glass for radiation resistance.

[0188] The radiation-resistant high-purity quartz glass prepared above was tested uniformly along the axial direction and the radial position of each axial cross section by a Fourier infrared tester, and the hydroxyl content thereof reached 900ppm±120ppm.

[0189] The results of atomic absorption spectrometer tests showed that the impurity content in the high-purity quartz glass for radiation resistance is less than 1 ppb.

[0190] The optical uniformity was tested by laser interferometer sampling and the value was 5.9ppm.

[0191] The prepared quartz rod is matched with fluorine-doped high-purity quartz glass for radiation resistance as a low refractive index cladding, and then prepared into an optical fiber preform rod and drawn into an optical fiber at high temperature. The optical fiber is then subjected to radiation treatment (total dose of 10KGy, 300Gy / h dose), and the typical attenuation values ​​of the optical fiber at 1310nm and 1550nm after radiation are 22.4dB / km and 20.3dB / km.

[0192] Comparative Example 2:

[0193] 1. Preparation of silica deposit: SiCl4, O2, H2, and Ar are introduced into the blowtorch, and the flame hydrolysis reaction produces SiO2 particles that are accumulated on the target rod, and the deposition is gradually lifted until the target rod is 1200mm long. During the deposition process, the rotation speed is 25rpm and the lifting speed is 1.0mm / min. The SiCl4 flow rate is 30g / min, the O2 flow rate is 15L / min, and the H2 flow rate is 45L / min. The deposition equipment is equipped with a blowtorch, an exhaust system, a pressure monitor, and a CCD camera diameter measurement system. The adjustable angle θ between the blowtorch axis and the target rod axis is 45°, the distance L1 between the blowtorch port and the target rod axis is 200mm, and the vertical distance between the blowtorch port and the target rod axis is L2, L2: L1 = 0.71. The air supply system consists of a high-efficiency filter (filtering particle size above 0.5um) and an automatic air supply structure, and the exhaust system is equipped with an automatic air supply structure. During the deposition process, the pressure controlled the negative pressure state and stabilized at 50pa. The ventilation was too large, the deposition efficiency was reduced, and the final powder rod diameter gradually changed from 115mm to 95mm, and the axial rod diameter fluctuated by 20mm. The CCD camera diameter measurement system mainly uses the CCD camera to realize online monitoring of the end shape of the silica deposit body, and calculates the diameter 2R of the silica deposit body and the distance h between the diameter change point and the end of the silica deposit body through software, and obtains h:R=1.28.

[0194] 2. Powder rod sintering: The sintering furnace is divided into two chambers, upper and lower. The upper chamber adopts metal shell, graphite heating, graphite insulation barrel and corrosion-resistant and high-temperature resistant metal inner layer (titanium alloy). The lower chamber is composed of shell, graphite heating body, graphite insulation barrel and quartz barrel. The heating zone length of the upper and lower chambers is the same, which is 1800mm. Gas is introduced from the bottom of the furnace body of the upper and lower chambers.

[0195] Pretreatment stage: fix the silica deposit on a hanger and place it in the upper chamber of the sintering furnace. The hanger rotates at 4.5rpm, and the temperature is quickly raised to 450°C. Oxygen pretreatment is directly carried out with an O2 flow rate of 4L / min. The positive pressure in the furnace is maintained at 20pa. The temperature is kept at a constant temperature in the furnace for 20 hours to obtain the first intermediate.

[0196] Vitrification stage: open the middle isolation plate, lower the first intermediate further into the lower chamber, keep the suspension rod rotation speed constant, keep the furnace temperature at 1400℃, O2 flow rate at 4L / min, He flow rate at 15L / min, keep the positive pressure at 20pa in the furnace, keep the temperature constant for 4h, and form a transparent glass rod. Release the furnace temperature, and stop introducing oxygen and He. When the pressure in the furnace is equal to the external environment pressure, close the pressure relief valve to obtain the second intermediate.

[0197] Purification stage: The second intermediate is raised to the upper chamber, the rotation speed of the boom remains unchanged, and the vacuum is directly turned on to a negative pressure of 0.4 bar. Then, a H2 and Ar mixed gas with a flow rate of 2L / min is introduced, where the H2 concentration is 0.5%, and the He flow rate is 3L / min. The positive pressure of the furnace is controlled at 0.25bar, and the temperature is controlled at 300℃. The temperature and pressure are kept constant for 60 hours, so that the hydrogen can be diffused in the high-purity quartz glass for radiation resistance.

[0198] The radiation-resistant high-purity quartz glass prepared above was tested uniformly along the axial direction and the radial position of each axial cross section using a Fourier transform infrared tester, and the hydroxyl content thereof reached 500ppm±100ppm.

[0199] The results of atomic absorption spectrometer tests showed that the impurity content in the high-purity quartz glass for radiation resistance is less than 1 ppb.

[0200] The optical uniformity was tested by laser interferometer and was found to be 6.5 ppm.

[0201] The prepared quartz rod is matched with polystyrene resin as a low refractive index cladding, and then the optical fiber is drawn at high temperature after being prepared into an optical fiber preform. The optical fiber is then subjected to radiation treatment (total dose of 10KGy, 300Gy / h dose), and the typical attenuation values ​​of the optical fiber at 1310nm and 1550nm after radiation are 24.4dB / km and 26.2dB / km.

[0202] Comparative Example 3:

[0203] 1. Preparation of silica deposit: SiCl4, O2, H2, and Ar are introduced into the blowtorch, and the flame hydrolysis reaction produces SiO2 particles that accumulate on the target rod, and the deposition is gradually lifted until the target rod is 1200mm long. During the deposition process, the rotation speed is 25rpm and the lifting speed is 1.0mm / min. The SiCl4 flow rate is 40g / min, the O2 flow rate is 30L / min, and the H2 flow rate is 80L / min. The deposition equipment is equipped with a blowtorch, an exhaust system, and a CCD camera diameter measurement system. The adjustable angle θ between the blowtorch axis and the target rod axis is 25°, the distance L1 between the blowtorch port and the target rod axis is 130mm, and the vertical distance between the blowtorch port and the target rod axis is L2, L2: L1 = 0.42. The pressure in the chamber is 35-65pa, and the final powder rod diameter gradually changes from 148mm to 120mm, and the axial rod diameter fluctuates to 28mm. The CCD camera diameter measurement system mainly uses a CCD camera to online monitor the end shape of the silica deposit, and calculates the diameter 2R of the silica deposit and the distance h between the diameter change point and the end of the silica deposit through software, and it can be obtained that h:R=0.85.

[0204] 2. Powder rod sintering: The sintering furnace is divided into a single chamber, which is composed of an outer shell, a graphite heating body, a graphite insulation barrel and a quartz barrel. The length of the heating zone is 1800mm, and the gas is introduced from the bottom of the furnace body of the chamber.

[0205] ① Pretreatment stage: fix the silica deposit on the suspension rod and place it in the upper chamber of the sintering furnace. The suspension rod rotates at 4.5rpm, the temperature is quickly raised to 400℃, and water mist with a flow rate of 1200ml / h is directly introduced. The positive pressure in the furnace is maintained at 12pa and the temperature is kept constant for 6h to obtain the first intermediate.

[0206] ②Vitrification stage: Open the middle isolation plate, lower the first intermediate further into the lower chamber, keep the rotation speed of the suspension rod constant, keep the furnace temperature at 1400℃, keep the constant temperature for 4 hours, keep the positive pressure in the furnace at 12pa, and simultaneously introduce water mist flow rate of 1200ml / h and He flow rate of 25L / min to form a transparent glass rod. After the end, release the furnace temperature and stop introducing water mist and He. When the pressure in the furnace is equal to the external environmental pressure, close the pressure relief valve.

[0207] The radiation-resistant high-purity quartz glass rod prepared above was tested uniformly along the axial direction and the radial position of each axial cross section by a Fourier infrared tester, and the hydroxyl content thereof reached 150-350 ppm.

[0208] The results of atomic absorption spectrometer tests showed that the impurity content in the high-purity quartz glass for radiation resistance is less than 1 ppb.

[0209] The optical uniformity was tested by laser interferometer and was found to be 6.2ppm.

[0210] The prepared quartz rod is matched with fluorine-doped quartz as a low refractive index cladding, and then prepared into an optical fiber preform rod, and then the optical fiber is drawn at high temperature. The optical fiber is then subjected to radiation treatment (total dose of 10KGy, 300Gy / h dose), and the typical attenuation values ​​of the optical fiber at 1310nm and 1550nm after radiation are 32.5dB / km and 28.7dB / km.

[0211] Comparative Example 4:

[0212] 1. Preparation of silica deposit: SiCl4, O2, H2, and Ar are introduced into the blowtorch, and the flame hydrolysis reaction produces SiO2 particles that accumulate on the target rod, and the deposition is gradually lifted until the target rod is 1500mm long. During the deposition process, the rotation speed is 25rpm and the lifting speed is 2mm / min. The SiCl4 flow rate is 25g / min, the O2 flow rate is 60L / min, and the H2 flow rate is 60L / min. The deposition equipment is equipped with a blowtorch, an air supply system, an exhaust system, a pressure monitor, and a CCD camera diameter measurement system. The adjustable angle θ between the blowtorch axis and the target rod axis is 60°, the distance L1 between the blowtorch port and the target rod axis is 65mm, and the vertical distance between the blowtorch port and the target rod axis is L2, L2: L1 = 0.87. The air supply system consists of a high-efficiency filter (filtering particle size above 0.5um) and an automatic air supply structure, and the exhaust system is equipped with an automatic air supply structure. During the deposition process, the pressure controls the negative pressure state and stabilizes at 30pa. By collecting the pressure monitor value and the opening / closing degree signals of the air supply / exhaust valve to the PLC online monitoring integrated platform, and adjusting the opening and closing degree of the air supply system and the exhaust system, the pressure and airflow in the deposition chamber are stabilized, and the axial diameter of the powder rod is 120-135m. The CCD camera diameter measurement system mainly uses the CCD camera to realize online monitoring of the end shape of the silica deposit body, and calculates the diameter 2R of the silica deposit body and the distance h between the diameter change point and the end of the silica deposit body through software, and obtains h:R=1.18.

[0213] 2. Sintering of silica deposits: The sintering furnace is divided into two chambers, upper and lower. The upper chamber uses a metal shell, graphite heating, graphite insulation barrel and a corrosion-resistant and high-temperature resistant metal inner layer (titanium alloy). The lower chamber consists of a shell, a graphite heating body, a graphite insulation barrel and a quartz barrel. The heating zone length of the upper and lower chambers is the same, which is 1500mm. The furnace body of the upper and lower chambers has three gas inlets evenly distributed along the longitudinal direction, arranged in a cross manner.

[0214] The sintering process is divided into three steps as follows:

[0215] Pretreatment stage: A. Fix the powder rod on the hanger and place it in the upper chamber of the sintering furnace. The hanger rotates at 6rpm. Vacuum is drawn at room temperature with a negative pressure of 0.1bar for 1.5h. B. The temperature is quickly raised to 150℃, and water mist is introduced at a flow rate of 800ml / h. The positive pressure is maintained at 6pa and the temperature is kept constant for 4h. C. The temperature is quickly raised to 400℃, the water mist flow rate is maintained at 800ml / h, the O2 flow rate is 2L / min, the positive pressure in the furnace is maintained at 5pa, and the temperature is kept constant for 10h to obtain the first intermediate.

[0216] Vitrification stage: open the middle isolation plate, and further lower the first intermediate into the lower chamber. The rotation speed of the suspension rod remains unchanged, the furnace temperature is 1250℃, the temperature is constant for 4 hours, the positive pressure in the furnace is maintained at 5pa, and O2, water mist, and He are introduced simultaneously to form a transparent glass rod, wherein the O2 flow rate is 2L / min, the water mist flow rate is 800ml / h, and the He flow rate is 6L / min. After the end, the furnace temperature is depressurized, and the introduction of oxygen, water mist, and He is stopped. When the pressure in the furnace is equal to the external environmental pressure, the pressure relief valve is closed to obtain the second intermediate.

[0217] Purification stage: Raise the second intermediate to the upper chamber, keep the rotation speed of the boom unchanged, close the isolation plate at the same time, turn on N2 to force cooling to less than 100°C, and control the cooling time to 60 minutes. After cooling, evacuate to a negative pressure of 0.3 bar. Then, introduce a H2 and Ar mixed gas with a flow rate of 10L / min, where the H2 concentration is 0.8%, the He flow rate is 2L / min, the positive pressure of the furnace is controlled at 2.5 bar, and the temperature is raised to 1000°C at a heating rate of 15°C / min. Maintain constant temperature and pressure for 40 hours to allow hydrogen to diffuse in high-purity quartz glass for radiation resistance. Due to the low He flow rate, high mixed gas flow rate, and high pressure in the furnace during the hydrogen loading process, some tiny bubbles exist in the glass, resulting in poor appearance.

[0218] The radiation-resistant high-purity quartz glass rod prepared above was tested uniformly along the axial direction and the radial position of each axial cross section by a Fourier transform infrared tester, and the hydroxyl content thereof reached 620 ppm±80 ppm.

[0219] The results of atomic absorption spectrometer tests showed that the impurity content in the high-purity quartz glass for radiation resistance is less than 1 ppb.

[0220] The optical uniformity was tested by laser interferometer and was found to be 5.3 ppm.

[0221] The prepared quartz rod is matched with polystyrene resin as a low refractive index cladding, and then the optical fiber is drawn at high temperature after being prepared into an optical fiber preform. The optical fiber is then subjected to radiation treatment (total dose of 10KGy, 300Gy / h dose), and the typical attenuation values ​​of the optical fiber at 1310nm and 1550nm after radiation are 30.1dB / km and 29.4dB / km.

[0222] Comparative Example 5:

[0223] The deposition process is the same as that of Comparative Example 4. During the sintering pretreatment process, the vacuum pressure is too high. When the negative pressure is greater than 0.6 bar, the powder is prone to cracking and cannot be prepared subsequently.

[0224] Comparative Example 6

[0225] The preparation method of the radiation-resistant high-purity quartz glass in this comparative example is substantially the same as that in Example 1, except that θ is 55°, L1 is 190 mm, and L2:L1=0.82.

[0226] The radiation-resistant high-purity quartz glass prepared above was tested uniformly along the axial direction and the radial position of each axial cross section by a Fourier infrared tester, and the hydroxyl content thereof reached 1375ppm±30ppm.

[0227] The results of atomic absorption spectrometer tests showed that the impurity content in the high-purity quartz glass for radiation resistance is less than 1 ppb.

[0228] The optical uniformity was tested by laser interferometer and was measured to be 8.6ppm.

[0229] The quartz rod is matched with fluorine-doped high-purity quartz glass for radiation resistance as a low-refractive index cladding to prepare an optical fiber preform rod, and then the optical fiber is drawn at high temperature. The optical fiber is then subjected to radiation treatment (total dose of 10KGy, 300Gy / h dose), and the typical attenuation values ​​of the optical fiber at 1310nm and 1550nm after radiation are 21.2dB / km and 23.8dB / km.

[0230] Comparative Example 7

[0231] The preparation method of the radiation-resistant high-purity quartz glass in this comparative example is substantially the same as that in Example 1, except that in the flame hydrolysis reaction, the rotation speed of the target rod is 50 rpm, the deposition rate of silicon dioxide is 1.6 mm / min, the flow ratio of SiCl4 to O2 is 3:1, the flow ratio of H2 to O2 is 4:1, and the flow rate of SiCl4 is 20-60 g / min.

[0232] The radiation-resistant high-purity quartz glass prepared above was tested uniformly along the axial direction and the radial position of each axial cross section by a Fourier infrared tester, and the hydroxyl content thereof reached 850ppm±20ppm.

[0233] The results of atomic absorption spectrometer tests showed that the impurity content in the high-purity quartz glass for radiation resistance is less than 1 ppb.

[0234] The optical uniformity was tested by laser interferometer and was measured to be 7.8ppm.

[0235] The quartz rod is matched with fluorine-doped high-purity quartz glass for radiation resistance as a low-refractive index cladding to prepare an optical fiber preform rod, and then the optical fiber is drawn at high temperature. The optical fiber is then subjected to radiation treatment (total dose of 10KGy, 300Gy / h dose), and the typical attenuation values ​​of the optical fiber at 1310nm and 1550nm after radiation are 18.1dB / km and 20.5dB / km.

[0236] Comparative Example 8

[0237] The preparation method of the radiation-resistant high-purity quartz glass in this comparative example is substantially the same as that in Example 1, except that:

[0238] ① Pretreatment stage: A. Fix the powder rod on the suspension rod and place it in the upper chamber of the sintering furnace. The suspension rod rotates at 7rpm and vacuum is drawn at room temperature with a negative pressure of 0.6bar for 4h.

[0239] B. Rapidly raise the temperature to 450°C, introduce water mist at a flow rate of 500 ml / h, maintain a positive pressure of 7 Pa, and keep the temperature constant for 9 hours;

[0240] C. Then quickly raise the temperature to 700°C, maintain the water mist flow rate at 500ml / h, the O2 flow rate at 1L / min, maintain the positive pressure at 35Pa in the furnace, and keep the temperature constant for 10h to obtain the first intermediate.

[0241] The radiation-resistant high-purity quartz glass prepared above was tested uniformly along the axial direction and the radial position of each axial cross section by a Fourier infrared tester, and the hydroxyl content thereof reached 650ppm±25ppm.

[0242] The results of atomic absorption spectrometer tests showed that the impurity content in the high-purity quartz glass for radiation resistance is less than 1 ppb.

[0243] The optical uniformity was tested by laser interferometer sampling and the value was 5.7ppm.

[0244] The quartz rod is matched with fluorine-doped high-purity quartz glass for radiation resistance as a low-refractive index cladding to prepare an optical fiber preform rod, and then the optical fiber is drawn at high temperature. The optical fiber is then subjected to radiation treatment (total dose of 10KGy, 300Gy / h dose), and the typical attenuation values ​​of the optical fiber at 1310nm and 1550nm after radiation are 20.7dB / km and 25.1dB / km.

[0245] Comparative Example 9

[0246] The preparation method of the radiation-resistant high-purity quartz glass in this comparative example is substantially the same as that in Example 1, except that:

[0247] ②Vitrification stage: open the middle isolation plate, further lower the first intermediate into the lower chamber, keep the rotation speed of the suspension rod unchanged, keep the furnace temperature at 1600℃, keep the temperature constant for 3h, keep the positive pressure in the furnace at 10Pa, and introduce O2, water mist, and He simultaneously to form a transparent glass rod, where the O2 flow rate is 7L / min, the water mist flow rate is 4000ml / h, and the He flow rate is 26L / min. After the end, release the furnace temperature and stop introducing oxygen, water mist, and He. When the pressure in the furnace is equal to the external environmental pressure, close the pressure relief valve, and the second intermediate.

[0248] The radiation-resistant high-purity quartz glass prepared above was tested uniformly along the axial direction and the radial position of each axial cross section by a Fourier infrared tester, and the hydroxyl content thereof reached 730ppm±45ppm.

[0249] The results of atomic absorption spectrometer tests showed that the impurity content in the high-purity quartz glass for radiation resistance is less than 1 ppb.

[0250] The optical uniformity was tested by laser interferometer sampling and the value was 6.8ppm.

[0251] The quartz rod is matched with fluorine-doped high-purity quartz glass for radiation resistance as a low-refractive index cladding to prepare an optical fiber preform rod, and then the optical fiber is drawn at high temperature. The optical fiber is then subjected to radiation treatment (total dose of 10KGy, 300Gy / h dose), and the typical attenuation values ​​of the optical fiber at 1310nm and 1550nm after radiation are 22.1dB / km and 26.4dB / km.

[0252] Comparative Example 10

[0253] The preparation method of the radiation-resistant high-purity quartz glass in this comparative example is substantially the same as that in Example 1, except that:

[0254] ③ Purification stage: Raise the second intermediate to the upper chamber, keep the rotation speed of the boom unchanged, close the isolation plate at the same time, turn on N2 to force cooling to less than 100°C, and control the cooling time to 70 minutes. After cooling, evacuate to a negative pressure of 0.2 bar. Then, introduce a H2 and Ar mixed gas with a flow rate of 6L / min, where the H2 concentration is 0.5%, the He flow rate is 2L / min, the positive pressure of the furnace is controlled at 2.5bar, and the temperature is raised to 900°C at a heating rate of 8°C / min. Maintain constant temperature and pressure for 160 hours, so that hydrogen can diffuse in the high-purity quartz glass for radiation resistance.

[0255] The radiation-resistant high-purity quartz glass prepared above was tested uniformly along the axial direction and the radial position of each axial cross section by a Fourier infrared tester, and the hydroxyl content thereof reached 680ppm±28ppm.

[0256] The results of atomic absorption spectrometer tests showed that the impurity content in the high-purity quartz glass for radiation resistance is less than 1 ppb.

[0257] The optical uniformity was tested by laser interferometer sampling and the value was 6.6ppm.

[0258] The quartz rod is matched with fluorine-doped high-purity quartz glass for radiation resistance as a low-refractive index cladding to prepare an optical fiber preform rod, and then the optical fiber is drawn at high temperature. The optical fiber is then subjected to radiation treatment (total dose of 10KGy, 300Gy / h dose), and the typical attenuation values ​​of the optical fiber at 1310nm and 1550nm after radiation are 21.9dB / km and 23.4dB / km.

[0259] The radial hydroxyl content distribution of Example 1 and Comparative Example 1 is as follows: Figure 6 As shown, R1, R2, and R3 are any positions of the high-purity quartz glass for radiation resistance of Example 1 or Comparative Example 1 along the radial direction, and the corresponding cross section of the position is uniformly tested at 3 points from the center to the outside. The hydroxyl values ​​corresponding to the 3 points are approximately close, which means that the radial consistency of the position is good; similarly, the hydroxyl values ​​of the points at various positions along the axial direction are close, which represents the uniformity of the hydroxyl group in the axial direction. The closer the values ​​are, the more uniform the distribution of the hydroxyl content in the axial direction is.

[0260] The radial hydroxyl content distribution of Example 4 and Comparative Example 3 is as follows: Figure 7 As shown, R1, R2, and R3 are any positions of the high-purity quartz glass for radiation resistance of Example 1 or Comparative Example 1 along the radial direction, and the corresponding cross section of the position is uniformly tested at 3 points from the center to the outside. The hydroxyl values ​​corresponding to the 3 points are approximately close, which means that the radial consistency of the position is good; similarly, the hydroxyl values ​​of the points at various positions along the axial direction are close, which represents the uniformity of the hydroxyl group in the axial direction. The closer the values ​​are, the more uniform the distribution of the hydroxyl content in the axial direction is.

[0261] The axial rod diameter distribution of the silicon dioxide deposits of Example 2 and Comparative Example 1 is as follows: Figure 8 As shown in the figure, during the cavity deposition process, as the powder rod gradually grows, its volume in the cavity gradually increases, and the corresponding cavity pressure also changes. If the cavity pressure is unstable, causing the deposition gas flow to fluctuate, the powder deposition on the rod will change, causing the rod diameter to fluctuate. When the powder rod diameter fluctuates, during the vitrification sintering process, the axial and radial shrinkage ratios are different, causing internal stress, that is, stress defects in the quartz network structure, which is not conducive to radiation resistance. Figure 8 It can be seen that the diameter of the high-purity quartz glass rod for radiation resistance in Example 2 changes little with the length of the rod diameter, which is beneficial to reducing the internal stress of the high-purity quartz glass rod for radiation resistance and improving the radiation resistance.

[0262] The spectrum loss diagram of the optical fiber of Example 2 is as follows: Fig. 9 As shown, after the radiation-resistant high-purity quartz glass of Example 2 is irradiated, the smaller the value of each point on the overall curve is, the lower the attenuation loss is, that is, the better the radiation resistance is.

[0263] Test results

[0264] Table 1

[0265]

[0266]

[0267] Data Analysis:

[0268] By controlling the angle and spacing between the blowtorch and the target rod, the bottom of the powder rod can be made flat. The smaller the h / R, the flatter the bottom. The smaller the difference in thermal stress and shrinkage between the inner and outer ends of the glass rod in the radial region after the powder rod is sintered, the better the optical uniformity of the prepared glass, and the better the radiation resistance of the prepared optical fiber.

[0269] VAD deposition voltage control system ensures that the axial direction of the powder rod is uniform and does not change with the length of the rod, eliminates the shrinkage force difference caused by the axial dimension fluctuation during the vitrification of the powder rod, reduces stress defects in the glass, and improves radiation resistance;

[0270] During the powder rod sintering process, the voids in the powder body are removed to promote the high-temperature migration of water molecules and oxygen molecules under high pressure, and high-temperature heat treatment and H2-carrying passivation treatment are performed during the vitrification stage to form high-purity quartz glass with high OH content and uniform distribution for radiation resistance, which is beneficial to improve radiation resistance;

[0271] During the sintering process, He has good heat transfer function, which helps to make the temperature inside and outside the glass uniform, ensuring that oxygen, water molecules, and hydrogen molecules are evenly diffused into the rod body, achieving uniform distribution in the radial and axial directions.

[0272] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A high-purity quartz glass for radiation resistance, characterized in that: The radiation-resistant high-purity quartz glass includes hydroxyl groups, the mass content of which in the radiation-resistant high-purity quartz glass is greater than or equal to 300 ppm, the fluctuation of the axial hydroxyl mass content in the radiation-resistant high-purity quartz glass does not exceed 15 ppm, and the fluctuation of the radial hydroxyl mass content in the radiation-resistant high-purity quartz glass does not exceed 15 ppm.

2. The radiation-resistant high-purity quartz glass according to claim 1, characterized in that: The impurity content of the high-purity quartz glass for radiation resistance is less than 1 ppb, and the optical uniformity of the high-purity quartz glass for radiation resistance is 1-5 ppm.

3. A method for preparing the radiation-resistant high-purity quartz glass according to claim 1 or 2, characterized in that: The following steps are involved: 1) Under a negative pressure of 20-35 Pa, a mixed gas of SiCl4, O2, H2, and Ar is subjected to a flame hydrolysis reaction to obtain a silicon dioxide deposit; 2) The silicon dioxide deposit is sequentially subjected to pretreatment, vitrification treatment and purification treatment to obtain the radiation-resistant high-purity quartz glass.

4. The method for preparing radiation-resistant high-purity quartz glass according to claim 3, characterized in that: The length of the silica deposit is 900-1500 mm, the diameter 2R of the silica deposit is 100-300 mm, and the ratio of h to R is 0.1-0.8; wherein R is the radius of the silica deposit, and h is the distance between the diameter change point and the end of the silica deposit.

5. The method for preparing high-purity quartz glass for radiation resistance according to claim 3 or 4, characterized in that: Step 1) comprises the following steps: Under a negative pressure of 20-35 Pa, the mixed gas of SiCl4, O2, H2 and Ar is subjected to the flame hydrolysis reaction through a blowtorch to deposit silicon dioxide on the target rod to obtain the silicon dioxide deposit; The angle θ between the axis of the blowtorch and the axis of the target rod is 30-50°, the distance L1 between the port of the blowtorch and the axis of the target rod is 80-180 mm, and the vertical distance between the port of the blowtorch and the axis of the target rod is L2, L2:L1=0.5-0.

76.

6. The method for preparing high-purity quartz glass for radiation resistance according to claim 5, characterized in that: The rotation speed of the target rod is 10-40 rpm, and the deposition rate of silicon dioxide is 0.3-1.5 mm / min; The flow ratio of SiCl4 to O2 is (1-2):(2-1), the flow ratio of H2 to O2 is (1-3):1, and the flow rate of SiCl4 is 20-40g / min.

7. The method for preparing high-purity quartz glass for radiation resistance according to any one of claims 3 to 6, characterized in that: The pre-processing comprises the following steps: 1) rotating the silicon dioxide deposit at a rotation speed of 3-6 rpm under a negative pressure of 0.2-0.5 bar for 1-3 hours; 2) introducing water mist at a flow rate of 1000-3000 mL / h into the space where the silicon dioxide deposit is arranged at 200-400° C. and 8-15 Pa for 4-8 hours; Wherein, the particle size of the water mist is 3-10 μm; 3) At 300-600° C. and 10-30 Pa, introduce water mist at a flow rate of 1000-3000 mL / h and O2 at a flow rate of 2-6 L / min, maintain for 12-24 hours, and obtain a first intermediate.

8. The method for preparing high-purity quartz glass for radiation resistance according to claim 7, characterized in that: The vitrification process comprises the following steps: At 1300-1500°C, water mist with a flow rate of 1000-3000mL / h, O2 with a flow rate of 2-6L / min, and He with a flow rate of 8-25L / min are introduced into the space where the first intermediate is set, and maintained for 4-6h to obtain a second intermediate.

9. The method for preparing high-purity quartz glass for radiation resistance according to claim 8, characterized in that: The purification process comprises the following steps: The second intermediate is cooled to less than 100° C. for 30-60 min. After the second intermediate is cooled, a mixed gas of H2 and Ar at a flow rate of 3-5 L / min and a mixed gas of He at a flow rate of 3-5 L / min are introduced into the space where the second intermediate is set at a negative pressure of 0.3-0.6 bar until the pressure of the space is a positive pressure of 0.5-2 bar, and the temperature is increased to 400-800° C. at a heating rate of 10-20° C. / min, and the temperature and pressure are kept constant for 60-150 h to obtain the radiation-resistant high-purity quartz glass; Wherein, the volume proportion of H2 in the H2 and Ar mixed gas is 1-3%.

10. A device, characterized in that: It includes a flame hydrolysis reaction unit, a pretreatment unit, a vitrification treatment unit and a purification treatment unit; The flame hydrolysis reaction unit is used for the flame hydrolysis reaction; The preprocessing unit is used for the preprocessing; The vitrification treatment unit is used for the vitrification treatment; The purification treatment unit is used for the purification treatment.

11. An optical fiber, characterized in that: The optical fiber is made of the radiation-resistant high-purity quartz glass according to claim 1 or 2.